Performance Evaluation of Irrigation System in Cikeusik Irrigation Area, Cirebon Regency West Java Province - Amrizal Amrizal; Umboro Lasminto; Bahmid Tohari (Institut Teknologi Sepuluh Nopember, 2017)
West Java Province is known as an area that plays an important role in agricultural production in Indonesia. Cirebon is a district in West Java which is in the eastern part bordering Central Java. Many areas of irrigation or Irrigation Network who experience a decrease in performance, one of whom who experience decreased performance is Cikeusik Irrigation Area. This time, the Irrigation Cikeusik Management implemented by Balai Besar Wilayah Sungai (BBWS) Cimanuk Cisanggarung, Directorate General of Water Resources, Ministry of Public Works and Public Housing. The Irrigation Cikeusik receive water supplies from Dam Cikeusik in the Cisanggarung river with the area in 6899 Ha. The purpose of this research is to analyze and calculate what percentage in the performance of the Sub Regional Irrigation Maneunteung West and Sub Regional Irrigation Maneunteung East on irrigation area Cikuesik using the Regulation of the Minister of Public Works No. 32 / PRT / M / 2007 on Guidelines for Operation and Maintenance of Irrigation. Some aspects of the irrigation system set out in the Regulation of the Minister of Public Works No. 32 / PRT / M / 2007 are physical infrastructure, plant productivity, supporting facilities Maintenance Operation, Maintenance Organization Operations personnel, documentation and water user associations (P3A). The research method is by direct observation, questionnaire and test methods research is done by Structural Equation Modeling (SEM). The performance evaluation of irrigation systems shows the percentage of different figures. Assessment is based on a survey conducted in West Sub Maneunteung irrigation area is 75.95% and 71.70% based on the respondent data. A difference of 4.26%, thus the performance of the irrigation system is ranged between 71.70% up to 75.95% or an average of 73.82%. Assessment is based on a survey conducted in Sub irigation area East Maneunteung is 76.10%, while 72.41% of respondents based on the data.The difference of 3.69%, thus the performance of the irrigation system is ranged between 72.41% up to 76.10% or an average of 74.26%. Based on the percentage of those with regulation of the Minister Public Works No. 32/PRT/M/2007 condition Sub irrigation area West Maneunteng and East Maneunteung have good performance.